THE RELATIONSHIP BETWEEN TIME MANAGEMENT, LEARNING MOTIVATION, AND PARENT’S ATTENTION WITH MATHEMATICS LEARNING OUTCOMES OF EIGHT GRADE STUDENT OF SMP MUHAMMADIYAH 1 SEYEGAN SLEMAN - Uswatun Chasanah; Edi Prajitno (Universitas Ahmad Dahlan, 2017)
The result of the study in a low student is related to many factors. The relationship between time management, learning motivation, and parent’s attention are the factors possible that may be linked to learning outcomes. The research is intended to know about is there any positive correlation and significance or not between time management, learning motivation, and parent’s attention with mathematics learning outcomes of eight grade students of SMP Muhammadiyah 1 Seyegan Sleman odd semester in the academic year of 2016/2017. The population in this research was the students of VIII grade in SMP Muhammadiyah 1 Seyegan Sleman in the academic year of 2016/2017, consisted of class VIIIA, VIIIB, VIIIC totaling 86 students. Samples were taken from VIIIB and VIIIC as the research sample class and with the random sampling technique. The writer uses a questionnaire method to collect the data of time management, learning motivation, and parent’s attention, and test method to get the resulting learning of math. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and the test of independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed that there was a positive and significance relationship time management, learning motivation, and parent’s attention with mathematics learning outcomes in students class VIII in odd Semester of SMP Muhammadiyah 1 Seyegan Sleman in academic year of 2016/2017. It is showed by = and = so with R= 0,5528 and R2 = 0,3056 with , with SR , SR and SR ,SE , SE dan SE .